The Giant Radio Array for Neutrino Detection - Martineau Huynh, Olivier (2017)
The Giant Radio Array for Neutrino Detection (GRAND) is a planned arrayof ~2x10^{5} radio antennas deployed over ∼ 200 000 km^2 in a mountainous site. It aims primarly at detecting high-energy neutrinos via the observation of extensive air showers induced by the decay in the atmosphere of taus produced by the interaction of cosmic neutrinos under the Earth surface. GRAND aims at reaching a neutrino sensitivity of 5 x 10^{−11}E^{−2} GeV^{−1}cm^{−2} s^{−1}{sr−1} above 3x10^{16} eV. This ensures the detection of cosmogenic neutrinos in the most pessimistic source models, and ∼50 events per year are expected for the standard models. The instrument will also detect UHECRs and possibly FRBs. Here we show how our preliminary design should enable us to reach our sensitivity goals, and discuss the steps to be taken to achieve GRAND, while the compelling science case for GRAND is discussed in more details in [1].